A Diachronic Comparison of the Vai Script of Liberia (1834–2005). (12th February 2018) - Tykhostup, Olena; Kelly, Piers
This dataset provides the first comprehensive diachronic comparison of the Vai script of Liberia, as derived from sixteen sources dated between 1834 and 2005. The Vai syllabary was invented by non-literate speakers of a Mande language and is of interest to scholars in the fields of writing and cultural transmission as an emergent writing system. Script samples that entered the dataset were retrieved from a wide variety of published manuscripts. The compiled dataset tracks the evolution of the Vai script via archival records and has reuse potential across various fields of research.